Larval fish fauna of a sandy beach and an estuary on Okinawa Island, focusing on larval habitat utilization by the suborder Gobioidei - Maeda, Ken; Tachihara, Katsunori (Fisheries science, 2014)
The Ryukyu Archipelago has a diverse fish fauna, but there have been no comprehensive studies of the larval fish fauna of its coastal habitats. The present study therefore investigated the species composition of larval fish communities on the sandy beach of Sedake and in the estuary of Teima Stream at Oh-ura Bay on Okinawa Island. In total, 12,067 individuals comprising 131 or more species that belong to 114 genera and 48 families were collected at night using a small seine net from January to December 1999. The suborder Gobioidei was the dominant taxon in this collection (86 %) and comprised 53 or more species. Most gobioids were postflexion larvae of amphidromous and estuarine species, at the stage just before they recruited to their adult habitats. Body lengths showed little variance within species. This suggests that they do not spend most of their pelagic larval lives in the estuary and on the sandy beach. These environments appear to be the route by which pelagic larvae move to their adult habitats. However, Rhinogobius and Tridentiger postflexion larvae displayed greater variance in body length and development, suggesting that they stay near the shoreline throughout this larval period.